Evaluating service performance and customer satisfaction in coffee shops: A SERVPERF analysis - Arnie Villanueva; Ryan Tayco (Borneo Novelty Publishing, 2025)
Purpose – This study aims to assess the service performance of selected coffee shops in Dumaguete City using the five SERVPERF dimensions: tangibility, reliability, responsiveness, assurance, and empathy.Methodology/Design/Approach – A descriptive-correlational research design was used, involving two respondent groups: 13 shop personnel (owners and employees) and 120 customers across six coffee shops, totaling 133 participants.Findings – Customers rated service positively across all SERVPERF dimensions, particularly in tangibility, reliability, and staff courtesy. Owners and employees also expressed confidence in their service quality. Demographic factors such as age, sex, occupation, nationality, frequency of visits, and spending significantly influenced satisfaction. Established coffee shops were perceived as more reliable. The results highlight the importance of maintaining high service standards and understanding customer profiles to enhance satisfaction and loyalty.Originality/Value – This study offers localized insights into coffee shop service quality in Dumaguete City using the SERVPERF model, providing practical guidance for improving customer satisfaction and long-term loyalty in the local coffee shop industry.